2015
DOI: 10.1371/journal.pone.0116769
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes with Alternative Dosing Strategies for Piperacillin/Tazobactam: A Systematic Review and Meta-Analysis

Abstract: ObjectivesA better dosing strategy can improve clinical outcomes for patients. We sought to compare the extended or continuous infusion with conventional intermittent infusion of piperacillin/tazobactam, investigating which approach is better and worthy of recommendation for clinical use.MethodsArticles were gathered from PubMed, Web of Science, ProQuest, Science Direct, Cochrane, two Chinese literature databases (CNKI, Wan Fang Data) and related ICAAC and ACCP conferences. Randomized controlled and observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 35 publications
6
62
0
3
Order By: Relevance
“…The clinical benefits of the continuous infusion strategy are supported by the results of recent meta-analyses, especially for patients with a high sickness severity and infected by less-susceptible pathogens, such as nonfermenting Gram-negative bacilli (11)(12)(13). In our cohort, the infective organism was not identified for 19 of the 53 patients (35.8%).…”
supporting
confidence: 66%
“…The clinical benefits of the continuous infusion strategy are supported by the results of recent meta-analyses, especially for patients with a high sickness severity and infected by less-susceptible pathogens, such as nonfermenting Gram-negative bacilli (11)(12)(13). In our cohort, the infective organism was not identified for 19 of the 53 patients (35.8%).…”
supporting
confidence: 66%
“…Although quite a few of these have been conducted over time, they differ markedly in their inclusion/exclusion criteria, thus not necessarily allowing elucidation of the true effectiveness of nontraditional beta-lactam dosing regimens (4,18,(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102). Recent metaanalyses that focused on beta-lactams (Table 3) have mostly concluded that existing data were favorable for the use of specific or all beta-lactam agents by prolonged or continuous infusion in terms of clinical outcomes.…”
Section: Contemporary Studiesmentioning
confidence: 99%
“…However, the evidence for clinical outcome benefit from prolonged infusions of beta-lactam antibiotics is still inconsistently reported, and is yet to be established [34,46]. Meta-analyses of published studies support benefits of reduced length of ICU stay, improved clinical cure rate, [47,48] and/or reduced toxicity [49] with prolonged infusions. However, a recent large multicentre randomized study [45] reported no difference in patient outcomes when comparing continuous versus intermittent infusion of three beta-lactams in 420 patients with severe sepsis.…”
Section: Prolonged Infusionsmentioning
confidence: 99%